Using a technology-based intervention to promote weight loss in sedentary overweight or obese adults: a randomized controlled trial study design - Vaughn W Barry (Dove Medical Press, 2011)
Vaughn W Barry1, Amanda C McClain1, Sara Shuger1, Xuemei Sui1, James W Hardin2, Gregory A Hand1, Sara Wilcox1, Steven N Blair1,21Department of Exercise Science; 2Department of Epidemiology and Biostatistics, University of South Carolina, Columbia, SC, USAPurpose: The SenseWear™ Armband is an activity monitor developed to improve lifestyle self-monitoring. Currently, few studies assess electronic self-monitoring and weight loss with a lifestyle intervention program. To our knowledge, only one study has used the SenseWear Armband in combination with a lifestyle intervention to improve weight loss, and no studies have evaluated whether a self-monitoring intervention based solely on the armband can promote weight loss. Consequently, the aims of the study were to assess weight loss from electronic self-monitoring, to compare these values to the lifestyle intervention and standard care groups, and to compare weight loss with lifestyle intervention with and without the armband.Patients and methods: We recruited 197 sedentary overweight or obese adults (age, 46.8 ± 10.8 years; BMI, 33.3 ± 5.2 kg/m2) to participate in the 9-month study. Participants were randomized into one of four weight loss groups: 1) the standard care group received a self-directed weight loss program, complete with an evidence-based weight loss manual (standard care, n = 50); 2) a 14-week group-based behavioral weight loss program followed by weekly, biweekly, and monthly telephone counseling calls (GWL, n = 49); 3) the use of the armband to help improve lifestyle self-monitoring (SWA alone, n = 49); or (4) the group-based behavioral weight loss program and follow-up telephone counseling calls plus the armband (GWL + SWA, n = 49). All participants received the evidence-based weight loss manual at baseline. All measures were performed at baseline and months 4 and 9. The primary outcomes were weight loss and waist circumference reduction.Results: This study is a well-designed randomized controlled study powered to detect a 0.5-kg weight loss and 0.6-cm waist circumference reduction in overweight and obese sedentary adults.Conclusion: Innovative technologies are providing lifestyle self-monitoring and weight loss tools. Utilizing these technologies may be an important step in improving the current obesity epidemic.Keywords: lifestyle, energy balance, behavioral education, accelerometer, SenseWear™ Armband